Estabilidade térmica, oxidativa e suporte em sílica mesoporosa de líquidos iônicos derivados do ibuprofeno - Wust, Keli Maiara (2018)
In this work, the thermal and oxidative stability of a series of ionic liquids (ILs) derived from active pharmaceutical ingredients (IL-APIs) with ibuprofen anion and cations: ranitidine [RAN][IBU], lidocaine [LID][IBU], bupivacaine [BUP][IBU] and diphenhydramine [DIP][IBU] were evaluated. The decomposition was determined by thermal and oxidative methods with and without hydrogen peroxide (H2O2) under UV-C radiation. The results showed that IL-APIs are thermally stable up to 160 °C, and have an activation energy of 60-100 kJ mol-1 for thermal decomposition, that is, requires energy consumption to initiate decomposition. Under isothermal conditions, the IL-APIs are stable up to 50 °C, however, fully decomposed after 24h, at 100 °C. The half-life times, obtained for the 20-40 °C range, showed that IL-APIs can take days (t1/2 = 18-72) for years (t1/2 = 13-35) to be decomposed. On the other hand, oxidative decomposition in water with and without H2O2 was faster (t1/2 = 4-12 min and 2-5h, respectively), resulting in the decomposition of IL-APIs from minutes to hours. The same IL-APIs were then supported on mesopours silica with 60 Å and 90 Å pores by a simple and efficient (adsorption from solution) process in the proportions 10, 20 and 50 wt%. Characterization techniques did not indicate changes in crystallinity of the supported materials. On the other hand, scanning and thansmission electron microscopy images show variations in the morphology of silica after adsorption of IL-APIs. The thermal stability of the supported IL-APIs on silica 60 Å had an increase up to the ratio of 20 wt%, and when supported on silica 90 Å, increase only in the proportion 10 wt%, which indicated changes in interaction with the change in pore size. The N2 adsorption/desorption technique, showed that the support of the IL-APIs occurs by the adsorption in pores of the silica because it indicates that after the support occurred the decrease of the specific area and volume of the pores. The release profiles were evaluated by the dialysis bag method in two dissolution media, and were shown to be sustained since the burst effect was not observed. The anti-inflammatory activity of IL-APIs was tested and showed that IL-APIs [DIP][IBU] had nociceptive activity, more effective than ibuprofenate sodium, 99.6% and 46.25, respectively. Based on this, this IL-APIs was supported on silica MCM-41 e SBA-15 in proportion 20 wt%. Characterization techniques did not indicate changes in crystallinity of the supported materials. Thermal stability increased only when [DIP][IBU] was supported on SBA-15, increasing by 59 °C over pure IL-APIs. The N2 adsorption/desorption technique proved the adsorption of the IL-APIs in the silica pores, as there was a 37% reduction in pore volume for SBA-15 and 44% for MCM-41. The release in two media showed that silica SBA-1 (81%) is capable of releasing larger amounts of IL-APIs than MCM-41 (74%).